P. 1

4.77

|Views: 35,090|Likes:
The Free High School Science Texts: Textbooks for High School Students Studying the Sciences Physics Grade 12 Copyright c 2007 “Free High School Science Texts” Permission is granted to copy, distribute and/or modify this document under the terms of the GNU Free Documentation License, Version 1.2 or any later version published by the Free Software Foundation; with no Invariant Sections, no Front- Cover Texts, and no Back-Cover Texts. A copy of the license is included in the section entitled “GNU Free Documentation License” Webpage: http://www.fhsst.org/
The Free High School Science Texts: Textbooks for High School Students Studying the Sciences Physics Grade 12 Copyright c 2007 “Free High School Science Texts” Permission is granted to copy, distribute and/or modify this document under the terms of the GNU Free Documentation License, Version 1.2 or any later version published by the Free Software Foundation; with no Invariant Sections, no Front- Cover Texts, and no Back-Cover Texts. A copy of the license is included in the section entitled “GNU Free Documentation License” Webpage: http://www.fhsst.org/

Availability:

See more
See less

10/14/2014

pdf

text

original

One of the most useful results of the trigonometric functions is that they are related to each
other. We have seen that tanθ can be written in terms of sinθ and cosθ. Similarly, we shall

show that:

sin2

θ + cos2

θ = 1

We shall start by considering △ABC,

A

B

C

θ

We see that:

sinθ = AC
BC

and

cosθ = AB
BC.

We also know from the Theorem of Pythagoras that:

AB2

+AC2

= BC2
.

So we can write:

sin2

θ + cos2

θ =

AC
BC

2

+

AB
BC

2

= AC2

BC2 + AB2
BC2

= AC2

+AB2

BC2

= BC2
BC2

(from Pythagoras)

= 1

392

CHAPTER 32. TRIGONOMETRY - GRADE 11

32.3

Worked Example 133: Trigonometric Identities A

Question: Simplify using identities:

1. tan2

θ·cos2

θ

2. 1
cos2

θ −tan2

θ

Step 1 : Use known identities to replace tanθ

= tan2

θ·cos2

θ

= sin2

θ

cos2

θ ·cos2

θ

= sin2

θ

Step 2 : Use known identities to replace tanθ

= 1
cos2

θ −tan2

θ

= 1
cos2

θ − sin2

θ

cos2

θ

= 1−sin2

θ

cos2

θ

= cos2

θ

cos2

θ = 1

Worked Example 134: Trigonometric Identities B

Question: Prove: 1−sinx

cosx = cosx
1+sinx

LHS = 1−sinx
cosx

= 1−sinx

cosx × 1 + sinx
1 + sinx

= 1−sin2

x

cosx(1 + sinx)

=

cos2

x

cosx(1 + sinx)

= cosx

1 + sinx = RHS

Exercise: Trigonometric identities

393

32.3

CHAPTER 32. TRIGONOMETRY - GRADE 11

1. Simplify the following using the fundamental trigonometric identities:

A cosθ
tanθ

B cos2

θ.tan2

θ + tan2

θ.sin2

θ

C 1−tan2

θ.sin2

θ

D 1−sinθ.cosθ.tanθ

E 1−sin2

θ

F

1−cos2

θ

cos2

θ

−cos2

θ

2. Prove the following:

A 1+sinθ

cosθ = cosθ
1−sinθ

B sin2

θ + (cosθ−tanθ)(cosθ + tanθ) = 1−tan2

θ

C (2cos2

θ−1)

1

+ 1
(1+tan2

θ) = 1−tan2

θ

1+tan2

θ

D 1

cosθ − cosθtan2

θ

1

= 1

E 2sinθcosθ

sinθ+cosθ = sinθ + cosθ− 1

sinθ+cosθ

F

cosθ

sinθ + tanθ

·cosθ = 1

sinθ

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->